(untitled) (Nepalese Veterinary Journal, 2018)
Peste des petits ruminant (PPR) is a common, acute, highly contagious and infectious viral epidemic disease of small ruminants which has caused significant economic losses in Nepal. Total of 247 suspected serum samples from 13 outbreaks from 8 districts of the Midwestern region of Nepal in 2015 were confirmed by using antibody ELISA test and in case of dead animals, the tissue samples were further confirmed by using antigen ELISA test. Out of 247 serum samples, 153 (61.9%) samples showed PPR antibody positive. The Ecozone wise distribution of PPR showed that the PPR outbreak were reported the highest in mountain followed by hills and the lowest in Terai. The highest outbreaks in mountain may be due to excessive movements of nomadic herd of sheep and goat, common pasture, low vaccine coverage in mountain whilst in hill region due to geographic difficulty and low sero-conversion of vaccine. Hence, strategic vaccination campaigns, proper biosecurity, movement control, risk analysis and early diagnosis need to be implemented for the control of PPR in the country.